1990
DOI: 10.1159/000267051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Optical Defocus on the Steady State Pattern Reversal Visual-Evoked Response

Abstract: The effects of optical defocusing with convex lenses on the amplitudes of pattern reversal visual-evoked response (PVER) were investigated. With the large check size and high-contrast pattern, PVER amplitudes showed a linear decrease in response to initial defocusing up to + 5 to + 6 dptr. As the degree of defocus increased, the PVER amplitude, though irregular, continued to show reliable, definite responses up to +25 dptr. With the intermediate check size and pattern contrast, PVER amplitudes displayed a line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…However, when volunteers with normal visual acuity were asked to perform a mental task (counting numbers), while viewing a pattern-reversal stimulus of 80 0 checks, the VEP responses were not affected [9]. Another possible maneuver that may lead to abnormal pattern VEP in subjects with normal vision is intentional defocusing of the visual target [9][10][11][12]. The reports that subjects can intentionally alter the pattern of their pattern VEP, and few of them managed to make it non-recordable [12,13], prevented this test from becoming an acceptable one for objective assessment of visual function.…”
Section: Introductionmentioning
confidence: 99%
“…However, when volunteers with normal visual acuity were asked to perform a mental task (counting numbers), while viewing a pattern-reversal stimulus of 80 0 checks, the VEP responses were not affected [9]. Another possible maneuver that may lead to abnormal pattern VEP in subjects with normal vision is intentional defocusing of the visual target [9][10][11][12]. The reports that subjects can intentionally alter the pattern of their pattern VEP, and few of them managed to make it non-recordable [12,13], prevented this test from becoming an acceptable one for objective assessment of visual function.…”
Section: Introductionmentioning
confidence: 99%
“…For the pattern VEP this has been repeatedly studied. It was shown that with intermediate check size amplitudes displayed a linear decrease and diminished down to noise level after a defocus of >+4 D to +5 D [11,4]. The effect of refractive blur has also been studied for the mfERG [1,6,14].…”
Section: Introductionmentioning
confidence: 99%
“…Since the interaction between the check size and the effect of defocusing on visual evoked cortical response has been demonstrated [11], this experiment was performed with refractive correction given to each subject. Most fMRI studies to date have been performed without appropriate refractive correction, probably due to the difficulty in using glasses for refractive correction in a magnet.…”
Section: Discussionmentioning
confidence: 99%